Knowledge, training and experience of advocates (lawyers) regarding medical malpractice laws in Pakistan - Saleem, Nayab; Aqeel Khan, Muhammad; Khan, Taza; Nisar, Adnan (ADVANCES IN BASIC MEDICAL SCIENCES, 2023)
Objective To assess knowledge, training and experience of Pakistani lawyers related to medical malpractice laws in the country. Methodology This descriptive, cross-sectional study was conducted among 190 advocates/lawyers registered and practicing law in district courts Peshawar, Pakistan. A 30 item, self-administered, structured questionnaire was first developed, validated and pilot tested to collect data on demographics, training, experience and knowledge of the advocates regarding medical malpractice laws in Pakistan. The knowledge score was calculated. Student t-test and Chi square test were used to assess the association ok knowledge score with experience and demographic characteristics. Results Majority of the respondents were male (70%), age 30 years or below (64.6%) and possess only undergraduate (LLB) qualification (82.1%). The mean knowledge score of the study participants was 5.8 ± 2.7. The knowledge score when categorized to low (participants scoring ≥ 6) or high (participants scoring < 6) was found significantly associated with gender (p=0.041), qualification (0.007) and training received (p=0.001). However, there was no significant differences in the knowledge score on the basis of age, practice speciality or experience. Conclusions The present study conclude that majority of the advocates possess limited knowledge about the medical malpractice laws in Pakistan. It is therefore crucial to include medical malpractice law in LLB curriculum and provide training opportunities to the lawyers in order to improve their knowledge and create awareness of medical malpractice laws in Pakistan. Keywords Malpractice, Negligence, Healthcare law, Medical Jurisprudence